Предмет: Алгебра,
автор: Vax69
помогите пожалуйста: упростите выражение (7x+1)(x-3)+20 (x-1)(x+1)=3 (3x-2)^2+13
Ответы
Автор ответа:
1
(7x+1)(x-3)+20 (x-1)(x+1)=3 (3x-2)²+13
7x²-21x+x-3+20(x²-1)=3(9x²-12x+4)+13
7x²-21x+x-3+20x²-20=27x²-36x+12+13
7x²-21x+x-3+20x²-20-27x²+36x-12-13=0
14x-28=0
14x=28
x=2
Похожие вопросы
Предмет: Химия,
автор: TypicalType
Предмет: Литература,
автор: anzelakorotka790
Предмет: Русский язык,
автор: miladnkrd
Предмет: Литература,
автор: лось46
Предмет: Информатика,
автор: FebriGuns